Developing Study Guides for Middle School Learners. Issue 2 (4th March 2017) - Conderman, Greg
ABSTRACT: Study guides are a popular tool teachers provide to help students prepare for an upcoming test or quiz. They are especially appropriate for middle school students as they transition from reading narrative to informational text. However, some teachers are unfamiliar with various types of study guides. Therefore, this article describes various types of study guides middle school teachers can develop to support student learning.